The Effectiveness of Cognitive Restructuring Techniques in Improving Students Learning Motivation - Astuti, Laily Puji; Wangid, Muhammad Nur (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
The aim of the research is to determine the effectiveness of cognitive restructuring techniques to increase learning motivation in students of State Islamic Junior High School 6 Bantul. The type of research is experimental research. The research design uses quasi-experiment. The design uses Non-equivalent Control Group Design. The research population was 8th grade students of State Islamic Junior High School 6 Bantul, amounting to 149 students. The sampling technique in the research used purposive sampling. The criteria for determining the sample in the research are students of State Islamic Junior High School 6 Bantul at 8th grade which indicated to have low learning motivation. The data collection method uses a scale of learning motivation that has gone through validation processes. Data analysis using non-parametric statistics with the Wilcoxon Signed Rank Test. The results showed that there were differences in the results of the experimental group's learning motivation before (M=72.17) and after (111.67) the treatment was given (p=0.027<0.05). These results can be concluded that cognitive restructuring techniques are effective to increase students learning motivation.